1949
DOI: 10.1002/jlac.19495610106
|View full text |Cite
|
Sign up to set email alerts
|

Natrium‐skatylsulfonat, ein Antagonist von Heteroauxin beim Wurzelwachstum

Abstract: 47X (a-P~enaceiylanzino-~-m~thox~~-propionyl)-S-henxyldzmefh~lc~stern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1951
1951
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Although compound 7 was previously synthesized by treatment of gramine with a sodium sulfite solution 48 , 49 or the sulfomethylation of indole with formaldehyde and sodium sulfite 50 and 8 was obtained from aerobic oxidation of indole-3-acetic acid with bisulfite 51 , 52 , 53 , the two compounds have never been isolated from a natural source. Thus, they are new natural products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although compound 7 was previously synthesized by treatment of gramine with a sodium sulfite solution 48 , 49 or the sulfomethylation of indole with formaldehyde and sodium sulfite 50 and 8 was obtained from aerobic oxidation of indole-3-acetic acid with bisulfite 51 , 52 , 53 , the two compounds have never been isolated from a natural source. Thus, they are new natural products.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they are new natural products. The detailed spectroscopic data of 7 and 8 are included in this paper since these data are absent in the literatures 48 , 49 , 50 , 51 , 52 , 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Sodium (indol-3-yl)methanesulfonate (1a) was obtained from gramine as previously described. 4,5 NMR spectra were recorded on a Varian VXR-400 instrument at 400 MHz ( 1 H NMR) in CD 3 OD, DMSO-d 6, or CDCl 3 using these solvents as internal standards [CDCl 3 : δ 1 H (residual) = 7.25, CD 3 OD: δ 1 H (residual) = 3.32, DMSO-d 6 : δ 1 H (residual) = 2.50]. Melting points were determined on a Büchi SMP-20 apparatus and are uncorrected.…”
Section: Reaction Of 13 and N-tert-butylmethanesulfonamidementioning
confidence: 99%
“…Initially, we sought an apparently direct route to this compound from sodium (indol-3-yl)methanesulfonate (1a). The synthesis of 1a from gramine has been described about 50 years ago, 4 however, no data about amides and other derivatives of this sulfonic acid have been published. Our first approach (pathway 1 in Scheme 1) was based on the attempt to transform 1a into the corresponding sulfonyl chloride 2a and then into sulfonamide 3a.…”
mentioning
confidence: 99%
“…The synthesis of one such compound, IMS,2 was first reported by Wieland et al (28) and it was subsequently shown to be biologically active in a variety of test systems (1,10,26,27). Sulfonic acids are considered strong acids with pKa values well below 0 (typically, negative 6.5 [18]) and as such exist essentially fully nonprotonated under physiological conditions.…”
mentioning
confidence: 99%